Evaluation of refuse-derived and tyre-derived fuels in cement industry: a study on emission characteristics - Cebeci, Havva Hande; Yucel, Ozgun; Sadikoglu, Hasan (INDERSCIENCE ENTERPRISES LTD, 2025)
This paper evaluates the impact of alternative fuels utilised in a cement facility in Central Anatolia, Turkey, on CO2, SO2, H2O, and NOx emissions. We implemented Chemkin-Pro and NASA CEA to investigate 16 fuel scenarios at temperatures between 973.15 K and 1,473.15 K. The modelling results demonstrate that high volatility and oxygen content in refuse-derived fuel contributed to an increase in NOx formation. Conversely, the low volatility and high carbon content of petcoke led to a decrease in NOx emissions. In scenario 13, the tyre and refuse-derived fuel combination yielded the lowest NOx emissions.
Keywords: alternative fuel; cement production; CO2 reduction; combustion gas emission; global warming; RDF; TDF; COMBUSTION; Environmental Sciences & Ecology